Molecular and serological detection of Leptospira interrogans among wild rats in flood-prone residential areas of Indonesia - Dewi Masyithah Darlan; Evita Mayasari; Sunna Vyatra Hutagalung; Ahadi Kurniawan; Ledy Afrida Sinaga; Alemina Pinem; Bernike Ambarita (Open Veterinary Journal)
Background: Indonesia is a tropical country with heavy rainfall, mostly in low-lying areas. Floods are one of the most common natural disasters in Indonesia, with climate change causing continuous flooding in some regions. The spread of human pathogens as a severe consequence of flooding, such as Leptospira, which may cause Weil's disease, is a concern for public health.